Development of Standard Test Specimens for Competency Improvement of Non-destructive Test (NDT) Personnel—Industrial Radiography - Sutanto, Jepri; Iswanto, Iswanto; Sumirat, Iwan; Pramutadi Andi Mustari, Asril; Permana, Sidik (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
Test specimens made of low-carbon SS400 steel in the form of plates and pipes will be manufactured for use by certification and training institutions. Currently, test specimens in Indonesia are imported, resulting in higher operational costs. Therefore, the domestic fabrication of test specimens is conducted to address this issue and improve the competency of NDT personnel. Radiographic techniques are applied to evaluate defects and verify acceptance criteria. Plate specimens with a geometry of 350 mm x 200 mm and pipes with a diameter of 2 "(50.8 mm) were welded using SMAW (Shielded Metal Arc Welding). Radiographic examinations revealed porosity and incomplete penetration (IP) defects on the plate specimens and four types of weld discontinuities on the pipe specimens: porosity, IP, external undercut, and spatter. The resulting density follows the acceptance standard, namely 2.12 on the plates and 1.91 on the pipes. Future evaluation using digital radiography methods such as computed radiography (CR) and digital detector arrays (DDA) is required to align with current technological advancements.